Enhancing Brand Image through Social Media Marketing and CSR: The Mediating Role of Consumer Trust in Indonesian Retail - Agustini, Triana; Endarwati, Esti Tri; Bassi, Aliming; Widarti, Widarti (Yayasan Sinergi Kawula Muda, 2025)
In Indonesian retail organizations, this study examines the effects of Social Media Marketing (SMM) and Corporate Social Responsibility (CSR) on Brand Image, with Consumer Trust as a mediating variable. With a sample size of 270, data were gathered quantitatively using a Likert scale (1–5), and structural equation modeling with partial least squares (SEM-PLS 3) was used for analysis. The findings show that SMM and CSR have a substantial positive direct impact on consumer trust, which significantly benefits brand image. Brand Image can be enhanced through substantial channels, as demonstrated by the indirect benefits of SMM and CSR through Consumer Trust. The model displays intense goodness of fit and predictive relevance, suggesting that SMM and CSR play critical roles in forming consumer trust and, in turn, brand image. These findings offer insightful information for retail businesses looking to enhance their brand image through socially conscious activities and strategic marketing.